The invisible students with disabilities in the Australian education system. Issue 6 (21st August 2017) - Teather, Susan; Hillman, Wendy
Abstract : Purpose: There has been very little empirical research for the need to identify the importance of an inclusive territory of commonality for "invisible" students with disabilities in Australian education testing, such as the National Assessment Program-Literacy and Numeracy (NAPLAN). The paper aims to discuss this issue. Design/methodology/approach: The research methodology used a cross-sectional mixed methods, deductive quantitative, an inductive qualitative, functionalist perspective and interpretivist perspective from internet secondary data analysis. This was undertaken to investigate the government functionalist macrosociology of Australian education to the detriment of the microsociology debate of students with disabilities, for inclusive education and social justice. Findings: This finding showed vastly underestimated numbers of students with disabilities in Australian schools experienced through "gatekeeping", non-participation in NAPLAN testing and choices of schools, resulting in poor educational outcomes and work-readiness. Social implications: The research findings showed that functionalism of Australian education is threatening not only social order, well-being and resilience of an innovative Australian economy through welfare dependency; but also depriving people with disabilities of social equality and empowerment against poverty brought about by a lack of education and of the human right to do a decent job. Originality/value: The study provided a critical evaluation of the weaknesses of government functionalism; specifically the relationship between the dualism of macro and micro perspectives, which promotes the existence of "invisible" students with disabilities in education, despite government legislation purporting an inclusive education for all students.